The intricacies of Acinetobacter baumannii: a multifaceted comprehensive review of a multidrug-resistant pathogen and its clinical significance and implications - Yehya, Amani; Ezzeddine, Zeinab; Chakkour, Mohamed; Dhaini, Zahraa; Bou Saba, Miriama S.; Bou Saba, Anthony S.; Nohra, Lea; Nassar, Nagham B.; Yassine, Mahdi; Bahmad, Hisham F.; Ghssein, Ghassan (Frontiers in Microbiology, 2025)
Acinetobacter baumannii, a highly adaptive and formidable nosocomial pathogen, has emerged as a symbol of modern medicine's struggle against multidrug resistance (MDR). As a Gram-negative dweller in moist hospital environments, A. baumannii has proven its ability to colonize the most vulnerable—critically ill patients—leaving behind a trail of infections highlighted by high morbidity and mortality and rendering nearly all antibiotics ineffective. This literature review aims to provide an in-depth, comprehensive overview of microbiological features, virulence factors, clinical manifestations, epidemiology, and antibiotic resistance mechanisms of A. baumannii. It also highlights the different diagnostic approaches, possible treatment strategies, and infection control, as well as the profound public health burden this pathogen imposes. The genus Acinetobacter has undergone a pivotal taxonomic journey and categorization. In addition, the intricate virulence mechanisms and factors of A. baumannii, including but not limited to outer membrane components and nutrient acquisition systems, have contributed to its pathogenicity and severe clinical manifestations ranging from respiratory tract infections and meningitis to urinary tract infections, skin infections, and bloodstream infections. This review also describes the epidemiological trend of A. baumannii established by its global prevalence and distribution, risk factors, hospital-acquired vs. community-acquired infections, and its geographical variations. In terms of antibiotic resistance, this pathogen has demonstrated resilience to a wide range of first-line and last-resort antibiotics due to its different evasion mechanisms. The current diagnostic approaches, treatment strategies, and infection control measures are further analyzed in detail, underscoring the need for prompt and precise identification of A. baumannii to guide appropriate therapy and reinforce the optimal approaches to limit its transmission and control outbreaks. Finally, the review addresses the substantial public health implications, reflecting on the hindrance that A. baumannii brings to healthcare systems, and the urgent need for global surveillance, effective infection control protocols, innovative research, and therapeutic approaches to mitigate its global threat.